2018
DOI: 10.1063/1.5017801
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure oriented carrier transport characteristic of triphenylamine derivative single crystal

Abstract: Organic electronic materials used in organic photoreceptors for electrophotography are expected to be employed in many functional organic devices. Regarding the inferior mobility compared to inorganic semiconductors, in this study, an organic single crystal was prepared at a high rate and characterized. First, solubility and supersolubility curves of α-phenyl-4’-[(4-methoxyphenyl)phenylamino]stilbene (TPA) were measured. According to the data, the rapid crystal growth has been succeeded. Polarization microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Triphenylamine derivatives have the following three important advantages: (i) they are low‐cost materials, (ii) a wide range of molecular designs is possible according to requirements, and (iii) their hole mobility is relatively high among representative hole transport materials. Moreover, we previously reported the successful preparation of single crystals of the triphenylamine derivative molecules, 4‐(2,2‐diphenylethenyl)‐ N , N ‐bis(4‐methylphenyl)‐benzenamine (TPA) and α‐phenyl‐4′‐[(4‐methoxyphenyl)phenylamino]stilbene, using a solution method based on their solubility and supersolubility curves, and demonstrated that their conductivities were ∼10 times greater than those of the amorphous forms .…”
Section: Introductionmentioning
confidence: 99%
“…Triphenylamine derivatives have the following three important advantages: (i) they are low‐cost materials, (ii) a wide range of molecular designs is possible according to requirements, and (iii) their hole mobility is relatively high among representative hole transport materials. Moreover, we previously reported the successful preparation of single crystals of the triphenylamine derivative molecules, 4‐(2,2‐diphenylethenyl)‐ N , N ‐bis(4‐methylphenyl)‐benzenamine (TPA) and α‐phenyl‐4′‐[(4‐methoxyphenyl)phenylamino]stilbene, using a solution method based on their solubility and supersolubility curves, and demonstrated that their conductivities were ∼10 times greater than those of the amorphous forms .…”
Section: Introductionmentioning
confidence: 99%
“…High hole mobility of the HTM and electron mobility of ETM layers are preferred for the fabrication of high‐performance OLEDs. The process of crystallisation is one method for regulating the charge‐carrier characteristics of organic materials because molecular ordering and the packing arrangement of the molecules in crystals play a huge role in modulating the charge‐transport abilities . The crystalline architectures that encompass higher degrees of intermolecular orbital overlap enhance the mobility of charges throughout the organic charge transporters .…”
Section: Introductionmentioning
confidence: 99%
“…The propeller‐shaped triphenylamine (TPA) core has gained immense interest for HTMs in OLEDs, owing to good thermal stability, a high glass transition temperature, and efficient hole‐transporting ability coupled with low ionisation potential . Functionalisation of the TPA molecule would result in diverse crystalline packing arrangements, which, in turn, could fine‐tune the optoelectronic properties of the core TPA moiety by enhancing the π–π interorbital interaction between phenyl rings . Thus, a thorough understanding of the interconnection between the molecular structure, packing arrangement and transport properties is indispensable in designing efficient and economical organic materials that are pertinent for optoelectronic devices …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations